Experimental Study on Acoustic Emission Characteristics of Intermittent Jointed Rock Mass Under Uniaxial Compression. (May 2019) - Zhu, Le; Zhang, Yan; Dong, Lu; Wu, Jiawen; Duan, Liqun; Zhang, Li
Abstract: Using large size of intact and intermittent jointed rocks made with equivalent materials, the stress-stain curves, ringing counts and energy accumulation of acoustic emission (AE) were obtained by AE monitoring in real time under uniaxial compression. The strength, deformation, progressive failure evolution and AE properties of two kinds of rock samples were compared. Through the analysis of AE parameters, the results indicate that the sudden increase of AE ringing counts and AE energy may be utilized as precursor information for the failure of rocks. AE location may directly reflect the dynamic evolvement process of rock cracks. Unlike the failure of intact rock sample, the AE ringing counts and energy curves of jointed rock sample show obvious multi-peaks, and the final peak appears behind the stress peak. The failure mode of intact rock is mainly vertical tensile breakage, whereas the tensile wing crack propagates through the joint surface, resulting in the failure of jointed rock sample.